La recente edizione di una traduzione trecentesca del De Civitate Dei - Fiorentino, Francesco (Augustinianum, 2016)
This article presents the recent edition which the research team, direct-ed by Olivier Bertrand, undertook in order to give back to the schol-arly community concerned with Augustine of Hippo the translation, in Middle French, by Raoul de Presles (1371-1375) of De civitate Dei commissioned by Charles V, the Good, King of France, while he was involved in the recapture of Brittany after the Treaty of Bretigny dur-ing the Hundred Years’ War. This translation, which originally enjoyed an enormous market success, has finally appeared in a critical edition consisting of five volumes. Until now, only the first two volumes have been available, containing, respectively, books I-III and IV-V.